The struggle against perceived negligence. A qualitative study of patients' experiences of adverse events in Norwegian hospitals - Gunn Hågensen; Gudrun Nilsen; Grete Mehus; Nils Henriksen (BMC, 2018)
Abstract Background Every year, 14 % of patients in Norwegian hospitals experience adverse events, which often have health-damaging consequences. The government, hospital management and health personnel attempt to minimize such events. Limited research on the first-hand experience of the patients affected is available. The aim of this study is to present patients' perspectives of the occurrence of, disclosure of, and healthcare organizations' responses to adverse events. Findings are discussed within a social constructivist framework and with reference to principles of open disclosure policy. Methods This qualitative study with an explorative descriptive design included fifteen in-depth interviews with former patients recruited by the Health and Social Services ombudsmen in the two northernmost counties of Norway. Inclusion criteria were as follows: 1) experience of adverse events in connection with surgical, orthopedic or medical treatment in general hospitals; 2) men and women; 3) aged 20-70; and 4) a minimum of one year since the event occurred. Transcribed audio-recorded interviews were analyzed through qualitative content analysis. Results The analysis revealed three main topics regarding patients' experiences of adverse events: 1) ignored concerns or signs of complications; 2) lack of responsibility and error correction; and 3) lack of support, loyalty and learning opportunities. Patients had to struggle to demonstrate the error that had occurred and to receive the necessary treatment and monitoring in the aftermath of the events. Conclusions Patient narratives reveal a lack of openness, care and responsibility in connection with adverse events. Conflicting power structures, attitudes and established procedures may inhibit prevention, learning and patient safety work in spite of major efforts and good intentions. Attitudes in day-to-day patient care and organizational procedures should be challenged to invite patients into open disclosure processes and include them in health and safety work to a greater extent. The study's small sample of self-selected participants limits the generalizability of the findings, and future studies should include a larger number of patients as well as professional perspectives.